Analysing the Malay Translation of Arabic Prohibition Sentences in the Poetic Theater Majnun Layla by Ahmad Shawqi - Wan Moharani Mohammad; Muhammad Marwan Ismail; Farah Nadia Harun; Nurhasma Muhamad Saad (Usuli Faqih Research Centre PLT, 2024)
Vol. 32 No. 2